Sarcoidosis Complicated by Cirrhosis and Hepatopulmonary Syndrome - Samir Gupta; Marie E Faughnan; Gerald J Prud’homme; David M Hwang; David G Munoz; Peter Kopplin (Canadian Respiratory Journal)
Sarcoidosis is a multisystem disorder commonly affecting the lungs, but also the liver, with cirrhosis and portal hypertension occurring in fewer than 1% of cases. Although hepatopulmonary syndrome (HPS) is seen in 15% to 20% of patients with cirrhosis of varying causes, it has rarely been associated with sarcoidosis. Also, although a brain abscess is not uncommon in patients with discrete pulmonary arteriovenous malformations, it is rarely seen in patients with the much smaller intrapulmonary vascular dilations that characterize HPS. A patient with an unusual series of uncommon sarcoidosis complications, including cirrhosis with HPS, brain abscess and finally Nocardia meningitis, is reported. The possibility of HPS should be considered in sarcoidosis patients with liver involvement, if gas-exchange abnormalities are out of proportion to the degree of lung involvement. These patients may also be susceptible to a cerebral abscess by paradoxical embolization, and to opportunistic infections due to cirrhosis.